2018
DOI: 10.1136/bmjopen-2018-024367
|View full text |Cite
|
Sign up to set email alerts
|

Reasons to stop drinking alcohol among patients with rheumatoid arthritis in Sweden: a mixed-methods study

Abstract: ObjectivesThe aims were to identify patients with rheumatoid arthritis (RA) who had stopped drinking alcohol and compare them with patients drinking alcohol, and to explore reasons for stopping drinking alcohol.DesignA sequential explanatory mixed methods design was used.SettingSix rheumatology clinics in Southern Sweden Better Anti-Rheumatic FarmacOTherapy cohort.ParticipantsA total of 1509 patients completed the questions about alcohol and were included in the study. 86 of these had stopped drinking alcohol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
1
5
0
1
Order By: Relevance
“…Another important reason justifying a recommended reduced alcohol consumption in RA is the indirect effects on bone tissue, which are related to the dose and duration of consumption. While moderate consumption (1–2 drinks per day) does not appear to be harmful to bone tissues, increased consumption could irreversibly damage bones and tendons [ 127 ].…”
Section: The Impact Of Lifestyle Changes In Ramentioning
confidence: 99%
“…Another important reason justifying a recommended reduced alcohol consumption in RA is the indirect effects on bone tissue, which are related to the dose and duration of consumption. While moderate consumption (1–2 drinks per day) does not appear to be harmful to bone tissues, increased consumption could irreversibly damage bones and tendons [ 127 ].…”
Section: The Impact Of Lifestyle Changes In Ramentioning
confidence: 99%
“…Based on the questionnaire of 2010 it was found that 6% of the patients had stopped drinking. By qualitative content analyses, we found that patients who stopped drinking were older, had lower health-related quality of life, more pain and fatigue and worse physical function compared with those who continued drinking 40. The reasons for stopping drinking alcohol varied but was most often illness.…”
Section: Major Resultsmentioning
confidence: 95%
“…The reasons for stopping drinking alcohol varied but was most often illness. Another reason was a desire to improve health and well-being and, less frequently, the patients referred to work and solidarity with family members 40…”
Section: Major Resultsmentioning
confidence: 99%
“…[7][8][9] One study linked alcohol consumption to increased radiological progression, however others associate drinking with milder disease activity. [10][11][12] This study examines the effects of alcohol consumption and its associations with remission and disease activity among 979 patients with inflammatory arthritis. Of the patients 64.2% were in remission.…”
Section: Rmd Open Rmd Open Rmd Openmentioning
confidence: 99%